1968
DOI: 10.1002/ijc.2910030118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microbial environment on development of myeloid leukemia in X‐irradiated rfm mice

Abstract: The incidence of radiation-induced myeloid leukemia, to which conventionally reared RF mice are unusually susceptible, has been observed to vary among colonies of RFM mice maintained in different microbial environments. The incidence in germ-free RFM males exposed to 300 R of X-irradiation at 5 to 6 weeks of age was only I %, whereas that in their conventionally reared counterparts was I3 %. In similarly irradiated RFM males subjected to microbial shock by transfer from an environment containing a limited numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…In¯ammatory responses can contribute to the development of leukaemia and may be particularly important in the development of radiation-induced leukaemias (Walburg et al, 1968;Yoshida et al, 1993). There is also evidence that radiation-induced genomic instability can be induced by an indirect mechanism (Lorimore et al, 1998;Watson et al, 2000) and that in both haemopoietic tissue (Watson et al, 1997) and mammary epithelium (Ponnaiya et al, 1997), there is genotype-dependent expression of the instability phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In¯ammatory responses can contribute to the development of leukaemia and may be particularly important in the development of radiation-induced leukaemias (Walburg et al, 1968;Yoshida et al, 1993). There is also evidence that radiation-induced genomic instability can be induced by an indirect mechanism (Lorimore et al, 1998;Watson et al, 2000) and that in both haemopoietic tissue (Watson et al, 1997) and mammary epithelium (Ponnaiya et al, 1997), there is genotype-dependent expression of the instability phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, even in this apparently simple model, radiation of a target stem cell is insufficient and may not even represent the tumourigenic event. In animal studies, leukaemia is not seen in irradiated mice that are housed under sterile conditions, demonstrating that ongoing inflammation is a requirement for disease progression [154,155]. Moreover, studies using non-transformed progenitor cells transplanted into irradiated recipients indicated that the primary radiation target is the haematopoietic microenvironment, not the cell that forms the leukaemia [156].…”
Section: Indirect Effects Of Dna-damaging Agentsmentioning
confidence: 99%
“…We report the ability to manipulate gametes and embryos from an inbred RFM/Ms mouse strain that has often been used in the study of leukemia [7,8]. In spite of the importance of this strain in radiation biology and immunology due to its high incidence of myeloid le uke m ia a ft er r adi at io n exp osu re [9,10 ], t he reproductive profile and gamete/zygote handling in vitro have not been studied.…”
Section: Abstract: In Vitro Fer Tilizability and Subsequent Developmementioning
confidence: 99%
“…In vitro handling, such as IVF and IVC is not necessarily possible in all inbred strains of mice [3][4][5][6]. The feasibility of IVF and IVC of a particular mouse strain has to be determined on a strain by strain basis in most cases.We report the ability to manipulate gametes and embryos from an inbred RFM/Ms mouse strain that has often been used in the study of leukemia [7,8]. In spite of the importance of this strain in radiation biology and immunology due to its high incidence of myeloid le uke m ia a ft er r adi at io n exp osu re [9,10 ], t he reproductive profile and gamete/zygote handling in vitro have not been studied.…”
mentioning
confidence: 99%